2021
DOI: 10.3389/fonc.2021.704339
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA KLF3-AS1 Acts as an Endogenous RNA of miR-223 to Attenuate Gastric Cancer Progression and Chemoresistance

Abstract: Gastric cancer is a deadly disease, and the low rate of early diagnosis and chemoresistance largely contributed to the poor prognosis of gastric cancer. LncRNAs have been extensively reported for their roles in regulating cancer progression. In this study, we found that KLF3-AS1 was down-regulated in gastric cancer cells. Overexpression of KLF3-AS1 repressed gastric cancer cell proliferation, growth. In addition, KLF3-AS1 overexpression also exerted inhibitory effects on the gastric cancer cell invasion, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 32 publications
0
11
4
Order By: Relevance
“…PCAT6 interference decreases cell viability and metastasis in OS 18 . However, in both ESCC and GC, the metastasis and proliferation of cancer cells may significantly be suppressed by KLF3‐AS1 overexpression 8,9 . Our results were opposite to these previous works as they indicated that knocking‐down KLF3‐AS1 did not only repress the in vitro cell proliferation, but it also limited in vivo tumor xenograft growth.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…PCAT6 interference decreases cell viability and metastasis in OS 18 . However, in both ESCC and GC, the metastasis and proliferation of cancer cells may significantly be suppressed by KLF3‐AS1 overexpression 8,9 . Our results were opposite to these previous works as they indicated that knocking‐down KLF3‐AS1 did not only repress the in vitro cell proliferation, but it also limited in vivo tumor xenograft growth.…”
Section: Discussioncontrasting
confidence: 97%
“…OS is one of the most prevalent bone malignancies among juveniles 16 . LncRNA KLF3‐AS1 is abnormally expressed and serves as an inhibitor in numerous human cancers, including ESCC 8 and GC 9 . In the current study, we demonstrated that, contrary to previous results, KLF3‐AS1 was overexpressed in OS cells and tumors.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Similarly, AC011462.4 was related with autophagy and veri ed with potential values on predicting renal cancer prognosis 36 . KLF3-AS1 can inhibit the expression of miR-223 to inhibit gastric cancer progression and resistance to chemotherapy 37 . What's more, KLF3-AS1 can attenuate miR-185-5p-mediated inhibition of KLF3 to impair cell migration and invasion 38 .…”
Section: Discussionmentioning
confidence: 99%